2020
DOI: 10.7759/cureus.6800
|View full text |Cite
|
Sign up to set email alerts
|

Undifferentiated Embryonal Sarcoma of the Liver Presents as a Molecular Mimic of Parasitic Infection

Abstract: Medical laboratory tests are becoming more reliable with increased specificity and sensitivity, leading to their use as definitive diagnostic tests for many medical conditions. Enzyme-linked immunosorbent assay (ELISA) tests are convenient, sensitive, and standardly used for rapid detection and quantification of antigens or patient antibodies against specific antigens. However, based upon the specificity and sensitivity of an ELISA test, the results may not be definitive for a specific disease but merely sugge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 10 publications
(12 reference statements)
0
4
0
Order By: Relevance
“…CT scans on the other hand show a predominantly cystic, hypoattenuated mass because the gel-like myxoid stroma has a water-like density when using CT. This discrepancy of a predominantly solid mass upon ultrasound and cystic mass upon CT is diagnostic of embryonal sarcoma [99,100]. Another characteristic feature is the presence of serpiginous vessels in the tumor in CT scans.…”
Section: Imaging Findingsmentioning
confidence: 98%
“…CT scans on the other hand show a predominantly cystic, hypoattenuated mass because the gel-like myxoid stroma has a water-like density when using CT. This discrepancy of a predominantly solid mass upon ultrasound and cystic mass upon CT is diagnostic of embryonal sarcoma [99,100]. Another characteristic feature is the presence of serpiginous vessels in the tumor in CT scans.…”
Section: Imaging Findingsmentioning
confidence: 98%
“…Patients may present with mild leukocytosis or leukopenia, anemia, hypoalbuminemia, mildly elevated transaminases, and inflammatory markers [ 160 , 163 , 167 ]. AFP and carcinoembryonic antigen are typically normal, although cases with elevated levels have been reported [ 159 , 160 , 161 , 163 , 164 , 165 , 168 ]. Interestingly, Letherer et al reported a case of a UESL in a 15-year-old male that caused a false positive ELISA result for Echinococcus , Entameoba histolytica , and histoplasmosis secondary to molecular mimicry [ 168 ].…”
Section: Malignant Tumors In School-aged Children and Adolescentsmentioning
confidence: 99%
“…AFP and carcinoembryonic antigen are typically normal, although cases with elevated levels have been reported [ 159 , 160 , 161 , 163 , 164 , 165 , 168 ]. Interestingly, Letherer et al reported a case of a UESL in a 15-year-old male that caused a false positive ELISA result for Echinococcus , Entameoba histolytica , and histoplasmosis secondary to molecular mimicry [ 168 ]. Zhang et al reported a case of a nine-year-old female with elevated IgE and transient peripheral eosinophilia, initially misdiagnosed as Echinococcus [ 165 ].…”
Section: Malignant Tumors In School-aged Children and Adolescentsmentioning
confidence: 99%
“…A crucial question for the future is to define mechanisms of molecular mimicry that exist between Taenia solium and neuronal antigens. At present, the only relevant observations are tenuous: (1) "Glycan mimicry" in many helminths, including Echinococcus granulosus and T. solium [7], (2) 94 tapeworm protein sequences with bioinformatic similarities to stickleback proteins [8] and (3) False positive ELISA's for E. granulosus with patients presenting with an undifferentiated embryonic sarcoma of the liver, interpreted as evidence for the molecular mimicry hypothesis [9].…”
mentioning
confidence: 99%